The Quest for Higher Growth in the WAEMU Region : The Role of Accelerations and Decelerations - Mlachila, Montfort; Kinda, Tidiane (Washington, D.C. : International Monetary Fund, 2011)
With the exception of Burkina Faso and Mali, the growth experience for WAEMU countries has been disappointing, even when compared to other sub-Saharan African (SSA) countries. The main objective of the paper is to investigate why the quest for a growth takeoff has been more elusive in the WAEMU countries compared to other SSA countries. To do this, the paper focuses on the determinants of growth accelerations and decelerations in SSA and the WAEMU. It finds that the variables most closely associated with growth accelerations and decelerations in SSA are changes in terms of trade, private investment, civil tension, real exchange rates, and inflation. Second, as found elsewhere in the literature, there is a certain asymmetry between accelerations and decelerations, in both frequency and determinants, and that the WAEMU region is quite different from the rest of SSA.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet